2019
DOI: 10.1002/jctb.5919
|View full text |Cite
|
Sign up to set email alerts
|

Determining butanol inhibition kinetics on the growth of Clostridium pasteurianum based on continuous operation and pulse substrate additions

Abstract: BACKGROUND Clostridium pasteurianum is a well described strain for the conversion of glycerol into butanol. In general, cell growth kinetics depends on the type of glycerol used and the concentration of butanol in the fermentation broth. However, despite the numerous studies existing on the subject, there is limited information in the literature regarding growth inhibition kinetics due to the cytotoxic effect of butanol on cell growth. This can be attributed to the difficulty of growing cells at high butanol c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…5 and 25 for the mesophilic and the thermophilic model, respectively (table 6). As shown in table 6, the datasets used for model calibration could not support the estimation of parameter combinations including both µmax and ks of the same microbial group, even when estimating only two parameters in the case of the mesophilic syngas biomethanation model [38,39]. Similarly, the importance of kLaH2 and kLaCO and their high collinearity with other parameters in both models would also limit the identifiability of other kinetic parameters if these were included, as other parameters would have to be fixed manually instead (table 6).…”
Section: Behavior Of Microbial Consortia and Yield Coefficients Consi...mentioning
confidence: 99%
“…5 and 25 for the mesophilic and the thermophilic model, respectively (table 6). As shown in table 6, the datasets used for model calibration could not support the estimation of parameter combinations including both µmax and ks of the same microbial group, even when estimating only two parameters in the case of the mesophilic syngas biomethanation model [38,39]. Similarly, the importance of kLaH2 and kLaCO and their high collinearity with other parameters in both models would also limit the identifiability of other kinetic parameters if these were included, as other parameters would have to be fixed manually instead (table 6).…”
Section: Behavior Of Microbial Consortia and Yield Coefficients Consi...mentioning
confidence: 99%
“…For example, potential production of n-butanol without the formation of acetone has been investigated using Clostridium pasteurianum. [41][42][43][44][45][46][47][48][49] All scientific peer-reviewed open literature revealed that the highest butanol concentration recorded for C. pasteurianum was 21 g/ L during mixed carbon source fermentation (1:1 glucose/glycerol). Even though the C. pasteurianum is unlike other clostridia (e.g., Clostridium beijerinckii) used to produce n-butanol, it generates 1,3-propanediol (1,3-PDO) as a major by-product.…”
mentioning
confidence: 99%